Treat and trick: common regulation and manipulation of sugar transporters during sink establishment by the plant and the pathogen - Pommerrenig, Benjamin; Müdsam, Christina; Kischka, Dominik; Neuhaus, H. Ekkehard (Journal of Experimental Botany, 2020)
Sugar transport proteins are crucial for the coordinated allocation of sugars. In this Expert View we summarize recent key findings of the roles and regulation of sugar transporters in inter- and intracellular transport by focusing on applied approaches, demonstrating how sucrose transporter activity may alter source and sink dynamics and their identities. The plant itself alters its sugar transport activity in a developmentally dependent manner to either establish or load endogenous sinks, for example, during tuber formation and filling. Pathogens represent aberrant sinks that trigger the plant to induce the same processes, resulting in loss of carbon assimilates. We explore common mechanisms of intrinsic, developmentally dependent processes and aberrant, pathogen-induced manipulation of sugar transport. Transporter activity may also be targeted by breeding or genetic modification approaches in crop plants to alter source and sink metabolism upon the overexpression or heterologous expression of these proteins. In addition, we highlight recent progress in the use of sugar analogs to study these processes in vivo.
CRIS-Team WoS Importer:2020-08-07